2013
DOI: 10.1111/imr.12067
|View full text |Cite
|
Sign up to set email alerts
|

Insights into B cells and HIV‐specific B‐cell responses in HIV‐infected individuals

Abstract: Human immunodeficiency virus (HIV) disease is associated with dysregulation and dysfunction involving all major lymphocyte populations, including B cells. Such perturbations occur early in the course of infection and are driven in large part by immune activation resulting from ongoing HIV replication leading to bystander effects on B cells. While most of the knowledge regarding immune cell abnormalities in HIV-infected individuals has been gained from studies conducted on the peripheral blood, it is clear that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
162
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(172 citation statements)
references
References 187 publications
(431 reference statements)
9
162
0
1
Order By: Relevance
“…CD4 + and CD8 + T cells, as well as NK cells, have significant noncytolytic functions that have not been included in our model. Our model also did not consider HIV-specific antibody responses (63,64) that could affect the details of the viral dynamic model in a number of ways (65). Whether these features of immune responses play a role in PTC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + and CD8 + T cells, as well as NK cells, have significant noncytolytic functions that have not been included in our model. Our model also did not consider HIV-specific antibody responses (63,64) that could affect the details of the viral dynamic model in a number of ways (65). Whether these features of immune responses play a role in PTC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-experienced B cells expressing CD27 can be differentiated into several distinct phenotypic and functional subsets based on lineage and differentiation markers, and the prevalence of these subpopulations is profoundly skewed in HIV infection (14,18). The dysregulation of the B cell compartment in HIV infection is likely caused by both direct immune stimulation and bystander mechanisms of immunologic damage (14); some of which persist in the presence of ART (15).…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of the B cell compartment in HIV infection is likely caused by both direct immune stimulation and bystander mechanisms of immunologic damage (14); some of which persist in the presence of ART (15). A recent study reported that bulk, non-antigen-specific RM B cells in peripheral blood are depleted during HIV infection, while AM and TLM cell frequencies expand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations